Hydrochemistry and Entropy-Based Groundwater Quality Assessment in the Suining Area, Southwestern China - Yunhui Zhang; Xiao Li; Ming Luo; Changli Wei; Xun Huang; Yong Xiao; Limao Qin; Qiuming Pei (Journal of Chemistry)
Groundwater is an essential resource for sustainable development, whose quality is significant for human health. In the present study, twenty-eight groundwater samples were collected from domestic tube wells and public water supply wells in the Suining area, southwestern China. The integration of statistical analysis, correlations of ions, geomodelling, and entropy-weighted water quality index (EWQI) was carried out to clarify the hydrochemistry and groundwater quality in the study area. By the statistical analysis, the cations followed the concentration order as Ca2+> Na+> Mg2+> K+, while anions’ concentrations were HCO3− > SO42− > Cl− > NO3− > F−. Piper trilinear diagram showed the hydrochemical type was characterized as Ca-HCO3. Correlations of ions and geomodelling revealed the concentrations of major ions were mainly determined by carbonate dissolution and ion exchange process, and NO3− concentrations were controlled by agriculture activities. EWQI computation demonstrated that most of the groundwater samples possessed EWQI values higher than 100. Therefore, groundwater quality is lower than the permissible limit of the World Health Organization (WHO), suitable for drinking purposes in the Suining area. Our study provides vital knowledge for groundwater management in the Suining and other similar areas.